THE IMPACT OF TECHNOLOGY ON THE DEVELOPMENT OF BALINESE SHADOW PUPPETRY IN THE GLOBAL ERA - Marajaya, I Made; Peradantha, Ida Bagus Gede Surya (Proceeding Bali-Bhuwana Waskita: Global Art Creativity Conference, 2024)
This study is motivated by the significant changes in Balinese shadow puppetry (wayang) resulting from the integration of technology in the global era. While the introduction of technology has opened new opportunities for the development of Balinese wayang, there are concerns that its use may undermine traditional values, affect the creativity of the puppeteers, and potentially threaten the preservation of this art form. Based on this, the study poses two main research questions: (1) How does technology influence the creativity of Balinese wayang in the global era? and (2) What are the impacts on the preservation and advancement of Balinese wayang? This qualitative research employs data collection methods such as observation, interviews, and literature review. The data were analyzed descriptively and interpretively, supported by creativity theory. The results indicate that technology has stimulated boundless innovation in Balinese wayang, leading to more engaging audio-visual performances. Moreover, the use of technology has contributed to the resurgence of the wayang-watching culture in Balinese society, while supporting the sustainability of this art form in the global era.